Obstacles to Exclusive Breastfeeding among Mothers Visit to Primary Health Care Centers in Basra Governorate - washih, Amal jabaar; Kazim, Fatima Nasser (American Journal of Biomedicine and Pharmacy, 2024)
The following research aims to examine Barriers to Exclusive Breastfeeding among Mothers attending the Primary Health Care Centers in Basra Governorate, Iraq. This study was designed to review and synthesis factors influencing timely exclusive breastfeeding practice. The study took the form of a questionnaire answered by 400 women with children, with questions about breastfeeding and the difficulties they experience. According to the study, the prevalence of exclusive breastfeeding among mother is 55% which is below the global allowance of 60%. Major hindrances revealed comprises of; inadequate milk supply (60%), working related issues (35%), traditional practices (25%). The analysis has shown that the level of education played the most important role in breastfeeding, where mothers with higher education levels practiced higher exclusive breastfeeding. Another characteristic of the employment status of the mother also affected the rate of breastfeeding; unemployed women had a higher tendency of engaging in exclusive breastfeeding than women who were employed. Socio-economic differences were recorded; working/urban mothers were found to exclusively breastfeed more than their counterpart, the rural/peri-urban mothers. Another social determinant that influenced breastfeeding was socio-economic; mom with higher income were most likely to practice exclusive breastfeeding. The study calls for the intervention strategies to remove such barriers such as education of mothers, workplace support and some cultural and economic problems. The results are beneficial in the development of future public health policies for exclusive breastfeeding and potential health benefits that may help of the health of mothers and infants in Basra Governorate.